The Analysis of Ferlin Hijab Customer Loyalty Through Price Perception, Business Location and Customer Service - yeseria maya Maulina, yeseria maya Maulina; Heri Purnomo,SE,MM, Heri Purnomo,SE,MM (Universitas Nusantara PGRI Kediri, 2025)
Research purposes :This study aims to analyze customer loyalty and its influence on customer service at Ferlin Hijab, price perception and its influence on customer service at Ferlin Hijab, and location and its influence on customer service at Ferlin Hijab. In addition, it is also to analyze customer loyalty, price perception, and business location and their influence on customer service at Ferlin Hijab simultaneously. Design/Method/Approach :This study is a quantitative method study by distributing questionnaires to 35 Ferlin Hijab customers as the sample size. The number of samples was determined by saturated sampling technique. Data analysis using SPSS software version 25. Research purposes:The results of the first hypothesis research are that customer loyalty has a positive and significant influence on Ferlin Hijab customer service. The second hypothesis is that price perception has a positive and significant influence on Ferlin Hijab customer service. The third hypothesis is that business location has a positive and significant influence on Ferlin Hijab customer service. And the fourth hypothesis is that customer loyalty, price perception, and business location have a positive and significant influence on Ferlin Hijab customer service. Theoretical contribution/Originality:This research contributes to developing customer service theory and to knowing what factors can influence customer service. Practical/Policy Implications:This study provides practical insights for Ferlin Hijab owners to determine affordable prices, choose strategic locations, and improve customer service. The results of this study can be used in designing business strategies to maintain customer service. Research Limitations:This research was only conducted in Ferlin Hijab, but the findings of this study do not reflect the overall condition of Ferlin Hijab. A wider number of samples or other studies with objects in hijab stores will be able to provide more representative research findings.